"Distinguishing Form": Shakespeare, Perspective and the Heartlessness of Comedy. (1st October 2020) - Yearling, Rebecca
ABSTRACT: Any discussion of comedy as a dramatic form is rendered difficult by the fact that the term "comedy" has two quite separate meanings: a work that is intended to make spectators laugh and a work that has a happy ending. In the early modern period, literary theorists were eager to make clear distinctions between the two definitions – in large part, because of the contemporary suspicion regarding the ethics of laughter, which was commonly seen as being related to cruelty. Theorists like Philip Sidney argued that we laugh at those to whom we feel superior, whereas a true comedy should aim to produce the rather different emotion of "delight". Modern critics are similarly prone to make distinctions between the "elevated" comedy of delight and the "low" comedy of laughter: the one rooted in an audience's sympathy towards the play's characters; the other in its amusement at those characters' follies. However, this essay will offer a different perspective. Through a consideration initially of The Winter's Tale, but also Shakespeare's earlier romantic comedies and problem plays, I will argue that the kind of 'delight' provoked by the end of much Shakespearean comedy often discourages a sense of true sympathy towards its subjects, and, indeed, may seem to share some of the heartlessness that Sidney saw as inherent in the comedy of laughter.